Kajian Literatur: Terapi Latihan fisik Aerobic terhadap Pasien dengan Skizofrenia - Wardany, Nadia Sintia; Sumartini, Sri; Dharmansyah, Dhika; Pragholapati, Andria (Jurnal Keperawatan Komplementer Holistic, 2025)
Schizophrenia is a chronic mental disorder that affects the emotional, cognitive, and social aspects of an individual, as well as the quality of life of patients. Conventional treatment is often inadequate to address the negative symptoms and cognitive deficits experienced by patients. Therefore, additional therapies such as aerobic exercise are gaining attention as non-pharmacological interventions that can improve treatment outcomes. Aerobic exercise has been shown to reduce negative symptoms, enhance cognitive function, and improve the quality of life for patients with schizophrenia. The underlying physiological mechanisms for these benefits include increased neuroplasticity, reduced inflammation, and elevated levels of brain-derived neurotrophic factor (BDNF). However, a major challenge in implementing this therapy is the low adherence rates of patients to structured physical exercise programs. This study employs a literature review approach to analyze and summarize research related to the effects of aerobic exercise on patients with schizophrenia. The findings of this review indicate that aerobic exercise therapy, whether as a standalone intervention or in combination, provides significant benefits to the cognitive function of patients. Further research is needed to understand the underlying mechanisms and to enhance the application of this therapy in the clinical management of schizophrenia.